Numerical Analysis of Anti-Slide Pile Reinforcement for Slope Stability Under Rainfall Conditions - Zhongyi Wen; Weiyuan Xu; Bingxiang Yuan; Lijuan Zhang; Zhu Liang (Buildings)
Rainfall-induced slope instability is a critical challenge in geotechnical engineering. This study investigates the reinforcement effect of anti-slide piles on slope stability under rainfall conditions using finite element numerical simulations, based on a slope reinforcement project in Youxi County, Fujian Province. The MIDAS GTS NX 2019(v1.2) software was employed to analyze the effects of anti-slide pile arrangements on slope safety factors, pore water pressure, displacement fields, and reinforcement effectiveness. The results showed that anti-slide piles significantly enhanced slope stability by mitigating the adverse effects of rainfall, such as an increased pore water pressure and reduced soil strength. The optimal stability was achieved when anti-slide piles were positioned in the middle sections of the slope, and the horizontal displacement in the x-direction was reduced from 74.49 mm (without reinforcement) to 7.42 mm, achieving a reduction of 90.0%, effectively reducing horizontal displacement and plastic strain zones. This study provides valuable insights into the interaction mechanisms between anti-slide piles and soil, offering practical guidance for slope reinforcement design and strategies to mitigate rainfall-induced slope failures.